Análise das características de perfil e dos indicadores de desempenho das universidades federais brasileiras - Flavia Silva de Lima Duque (2016)
The administrative autonomy of the Federal Institutions of Higher Education (IEFES), prerogative guaranteed by the Federal Constitution of 1988, can be an outlet to improve the performance of higher education. In contrast to greater autonomy, management responsibilities have also increased and are linked to evaluation. Contributing to the challenge of promoting accountability as a means of increasing transparency and improving the management of TCU. For this, the data were summarized by means of descriptive statistics and the associations were analyzed through the correlation matrix and the means test. The results of the study showed the great heterogeneity presented by the IFES, including institutions located in diverse economic and geographic realities and in different stages of life cycle. It was possible to confirm the general improvement trend of the profile variables and management indicators analyzed, mainly due to the expansion process of the REUNI program started in 2007. The correlations were positive and significant in relation to the associations between the approved budget and the performance The current cost per student equivalent and the relationships between students and teachers. The Southeast region presented the highest average for all variables analyzed, but regional differences were not significant in terms of cost per student and number of full-time students per equivalent teacher. The age of the organization is positively related to the postgraduate performance and the degree of commitment of the students, but it was negative in relation to the number of students and employees. The tendency of the IFES is a better performance of the TCU indicators as the number of students increases, but there are indications that the increase of equivalent students is accompanied by a rise in the number of employees that is higher than the increase of teachers. Thus, it was possible to verify that the simplicity of the set of indicators proposed by the TCU was sensitive to the different scenarios in which the IFES are inserted, which makes it difficult to evaluate and compare them, transforming the indicators into control instruments. Therefore, the IFES still have the challenge of looking for management indicators with property and dimensions that allow the improvement of the performance of the evaluated and the reflection, contributing to the planned application of predictive, anticipatory and corrective actions, while remaining simple and easy to to monitor.